(untitled) (Scientific journal of the Fergana State University, 2025)
We report a high-temperature colloidal synthesis of cadmium telluride (CdTe) quantum dots (QDs) enabling precise control over particle size and emission properties. By varying reaction conditions, including temperature, residence time, and precursor composition, we produced a series of CdTe QD samples emitting across the visible spectrum—from blue-green ( 480 nm) to deep red ( 665 nm)—under UV excitation. The samples, synthesized from cadmium acetate dihydrate and elemental tellurium in a mixture of trioctylphosphine (TOP), 1-octadecene (ODE), and oleic acid (OA), exhibit narrow size distributions, high photoluminescence quantum yields, and well-defined color transitions that confirm quantum confinement effects. These results underscore the effectiveness of high-temperature synthetic strategies for producing high-quality CdTe QDs suitable for advanced optoelectronic, bioimaging, and photovoltaic applications.